Persepsi Guru Sekolah Dasar Mengenai Implementasi Kurikulum Darurat Selama Masa Pandemi COVID-19 - Indriani, Suci; Julia, J.; Iswara, Prana Dwija (Jurnal Pena Ilmiah, 2021)
The emergency curriculum is a policy taken to adjust the implementation of learning activities during the COVID-19 pandemic. Teachers play a big role in implementing the policy.The implementation of learning activities during the COVID-19 pandemic depends on the performance of the teacher to implement the curriculum. This research was conducted in a survey through a questionnaire with 85 elementary school teacher participants inÂ  Sumedang Utara District in 2021. Data analysis was carried out descriptively. The results of this study are all elementary school teachers in Sumedang Utara District have good perceptions of the implementation of the emergency curriculum during the COVID-19 pandemic. It is shown from the results of the three aspects that have been researched; elementary school teachers with good knowledge of the emergency curriculum, the implementation of the emergency curriculum that is well implemented, and the perceived obstacles in the implementation of the emergency by elementary school teachers.